Banking Performance under the Lens of Earnings Management: A Theoretical and Bibliometric Systematic Review - Nyayu Khalilah Putri; Mohamad Adam; Isnurhadi Isnurhadi; Muizzuddin Muizzuddin (Institute of Multidisciplinary Research and Community Service, 2026)
This study conducts a systematic literature review (SLR) combined with bibliometric analysis to examine earnings management (EM) practices in the banking sector and their implications for financial performance. Following the PRISMA guidelines, the methodology employed a rigorous search strategy using specific keyword combinations, including